Fas’ın Idmine Ormanı’ndaki Bozulmuş Orman Alanlarının Yerbilim Yeteneklerini Kullanarak Mekansal Analizi - Laaribya, Said; Alaoui, Assmaa; Ayan, Sezgin; Benabou, Abdelkader (Kastamonu Üniversitesi, 2020)
Aim of study: The aim of the study is to present a diagnosis for the state of Argan forest degradation in Morocco through GIS and remote sensing utilizing Sentinel 2 satellite images of the year 2019 (dated 28/08/2019).Area of study: The study was carried out in a forest commune in Idmine, South West Morocco, which is located in semi-arid bioclimatic region.Material and methods: In the study, two methods were tested. These are; (i) the vegetation indices (VIs) [Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), Soil-Adjusted Vegetation Index (SAVI), Brilliance Index (IB)] and their combination and (ii) the supervised classification and spectral analysis.Main results: Two methods have given the same results (Kappa coefficient=90%) to describe the state of forest degradation. Consequently, three classes pertaining to forest degradation within the study area were; low (34%), medium (44%) and critical degradation (22%).Highlights: This monitoring might help managers to create forest management plans and to evaluate the speed of deforestation and degradation.

Çalışmanın Amacı: Çalışmanın amacı, 2019 yılının (28/08/2019 tarihli) Sentinel 2 uydu görüntülerini kullanarak CBS ve Uzaktan Algılama yoluyla orman bozulma durumu için bir tanı sunmaktır. Çalışma Alanı: Çalışma, yarı kurak biyoklimatik bölgede bulunan Güney Batı Fas'taki Idmine orman komününde gerçekleştirilmiştir. Materyal ve Yöntem: Bu çalışmada, iki yöntem denenmiştir. Bunlar; (i) Vejetasyon indisleri (VIs) [Normalize Fark Vejetasyon İndeksi (NDVI), Normalize Fark Su İndeksi (NDWI), Toprak-uyarlı Vejetasyon İndeksi (SAVI), Parlaklık İndeksi (IB)] ve bunların kombinasyonu ile (ii) Denetimli sınıflandırma ve spektral analizdir.Temel sonuçlar: Orman degradasyon durumunu tanımlamak için iki yöntem aynı sonuçları (Kappa katsayısı=%90) vermiştir. Sonuç olarak, çalışma alanı içindeki orman degredasyonuna ilişkin üç sınıf; düşük (%34), orta (%44) ve kritik bozulma (%22)’dır.Araştırma Vurguları: Bu izleme, yöneticilerin orman yönetim planları oluşturmasına ve ormansızlaşma ve orman degredasyonu hızını değerlendirmesine yardımcı olabilir.
Keywords: GIS; Remote Sensing; Vegetation Index; Degradation; CBS; Uzaktan Algılama; Vejetasyon Indeksi; Degradasyon; 13. Climate action; 15. Life on land